Phylogeography using mitogenomes: A rare Dipodidae, Sicista betulina, in North‐western Europe. Issue 4 (21st April 2022) - Andersen, Liselotte Wesley; Jacobsen, Magnus W.; Frydenberg, Jane; Møller, Julie Dahl; Jensen, Thomas Secher
Abstract: Repeated climatic and vegetation changes during the Pleistocene have shaped biodiversity in Northern Europe including Denmark. The Northern Birch Mouse ( Sicista betulina ) was one of the first small rodent species to colonize Denmark after the Late Glacial Maximum. This study analyses complete mitochondrial genomes and two nuclear genes of the Northern Birch Mouse to investigate the phylogeographical pattern in North‐western Europe and test whether the species colonized Denmark through several colonization events. The latter was prompt by (i) the present‐day distinct northern and southern Danish distribution and (ii) the subfossil record of Northern Birch Mouse, supporting early Weichselian colonization. Samples from Denmark, Norway, Sweden, Russia, Latvia, Estonia, and Slovakia were included. Mitogenomes were obtained from 54 individuals, all representing unique mitogenomes supporting high genetic variation. Bayesian phylogenetic analysis identified two distinct evolutionary linages in Northern Europe diverging within the Elster glaciation period. The results of the two nuclear genomes showed lower genetic differentiation but supported the same evolutionary history. This suggests an allopatric origin of the clades followed by secondary contact. Individuals from southern Denmark were only found in one clade, while individuals from other areas, including northern Denmark, were represented in both clades. Nevertheless, we found no evidence for repeated colonization's explaining the observed fragmented distribution of the species today. The results indicated that the mitogenome pattern of the Northern Birch Mouse population in southern Denmark was either (i) due to the population being founded from northern Denmark, (ii) a result of climatic and anthropogenic effects reducing population size increasing genetic drift or (iii) caused by sampling bias. Abstract : The phylogeographical pattern of the Northern Birch Mouse ( Sicista betulina ) in Northwestern Europe was investigated using complete mitochondrial genomes and two nuclear genes. Samples representing Denmark, Norway, Sweden, Russia, Latvia, Estonia and Slovakia were analysed. Mitogenomes were obtained from 54 individuals, all unique, supporting high genetic variation. Two distinct evolutionary linages diverging within the Elster glaciation period was found suggesting an allopatric origin and vicariance followed by secondary contact throughout the northern range. The results indicated that the mitogenome pattern of the Northern Birch Mouse population in southern Denmark was either (i) due to the population being founded from northern Denmark, (ii) a result of climatic and anthropogenic effects reducing population size increasing genetic drift or (iii) caused by sampling bias.